IMPLEMENTATION OF SCHOOL FEATURED PROGRAMS IN ACHIEVING STUDENT LEARNING ACHIEVEMENT AT STATE ISLAMIC JUNIOR HIGH SCHOOL STUDENTS - Reksiana Reksiana; Maura Indah Sapirna (Proceeding International Seminar of Islamic Studies, 2022)
The research aims to prove that the application of the superior class program at Mts Negeri 1 Lampung Selatan can achieve student achievement in the cognitive, affective, and psychomotor domains. The research method used is a qualitative method with descriptive analysis type. Primary sources come from the person in charge of the superior class section, such as the tahfiz teacher, and several top class students at MTs Negeri 1 South Lampung. The secondary sources are books, journals, thesis. And documentary sources in the form of observation results in the form of field notes during observations, interviews, photo and audio documentation. Data collection techniques in the form of observation, interviews, and documentation. And data analysis techniques using Miles Hubermen analysis through predetermined stages. The results of this study prove that the application of the superior class program at MTs Negeri 1 Lampung Selatan can achieve and even improve student learning achievement from several aspects. First, the cognitive aspect is seen from the success of learning in the classroom. Superior class students can understand learning materials well both inside and outside the classroom. Second, the affective aspect can be achieved in the attitude of students who respect each other. Then students have high enthusiasm/motivation to learn, and students have good morals. Third, the psychomotor aspect is reflected in students being able to practice the skills of learning activities both inside and outside the classroom well.Keywords: Implementation, School Featured Programs, Learning Achievement